PENGARUH GAME ONLINE TERHADAP KETAATAN BERIBADAH MAHASISWA DI JURUSAN PENDIDIKAN AGAMA ISLAM UNIVERSITAS MUHAMMADIYAH MALANG - Abdul Haris; Daniar Chandra Anggraini; Dina Mardiana (Universitas Tanjungpura, 2022)
AbstractThis research discusses the influence of online gaming on the obedience of students at department of Islamic Education of University of Muhammadiyah Malang, especially in students of the class of 2017 and 2018. This research is based on the excessive intensity of online gaming that affects the obedience of student worship. This research is using field research, with a type of quantitative research. The sampling technique used in this study was Simple Random Sampling with 52 respondents. While data collection technique using questionnaire methods. The results of the correlation coefficient significant test using product moment correlation analysis the result was -0,276 < 0,279 < 0,361. The meaning is there is no positive and significant correlation between the intensity of online gaming to the obedience of students at the Department of Islamic Education of University of Muhammadiyah Malang.Keywords: Online Games, Obedience to Worship